A Group of Expressed cDNA Sequences from the Wheat Fungal Leaf Blotch Pathogen, Mycosphaerella graminicola (Septoria tritici) - Keon, J.; Bailey, A.; Hargreaves, J.
Keon, J., Bailey, A., and Hargreaves, J. 2000. A group of expressed cDNA sequences from the wheat fungal leaf blotch pathogen, Mycosphaerella graminicola (Septoria tritici). A group of expressed sequence tags (ESTs)from the wheat fungal pathogen Mycosphaerella graminicola utilizing ammonium as a nitrogen source has been analyzed. Single pass sequences of complementary DNAs from 986 clones were determined. Contig analysis and sequence comparisons allowed 704 unique ESTs (unigenes)to be identified, of which 148 appeared as multiple copies. Searches of the nrdb95 protein database at EMBL using the BLAST2x algorithm revealed 407 (57.8
Keywords: CDNAS; EXPRESSED SEQUENCE TAGS; MYCOSPHAERELLA GRAMINICOLA; PLANT PATHOGEN; WHEAT